Influencing Factors of Resorption in Lumbar Disc Herniation - SHEN Xueqiang; LIU Jintao; YU Pengfei; DAI feng; ZHU Yu; JIANG Hong (康复学报, 2022)
ObjectiveTo investigate the influencing factors of resorption in lumbar disc herniation (LDH).MethodsA total of 116 patients with LDH who were hospitalized in Suzhou Hospital of Traditional Chinese Medicine Affiliated to Nanjing University of Chinese Medicine from April 2016 to December 2019 with non-surgical plan as the first treatment choice were selected and retrospectively analyzed. According to whether the resorption occurred at the last follow-up, the patients were divided into reabsorption group (45 cases) and non-reabsorption group (71 cases). The relevant data of the two groups were collected, including demographic and clinical factors (age, course of disease, gender), degree of LDH (Komori classification), tissue composition of LDH [Iwabuchi classification, LDH Pfirrmann classification, MRI relative signal intensity (RSI)], and MRI imaging characteristics (Modic changes in adjacent vertebral bodies, spinal canal morphology, horsetail sedimentation sign Schizas classification). Univariate analysis was conducted to find the indicators with statistical differences between the two groups, which were further analyzed by logistic regression to determine whether they were independent factors affecting the resorption of LDH.ResultsThe symptoms of 45 patients with resorption significantly improved, and of the 71 patients without resorption, 23 patients underwent surgery. There were significant differences between the two groups in age, course of disease, Komori classification, Iwabuchi classification, Pfirrmann classification, RSI, Modic changes, spinal canal morphology and horsetail sedimentation sign Schizas classification (P<0.05). Further logistic analysis demonstrated that the course of disease, Komori classification, Iwabuchi classification, RSI, Modic changes were independent factors affecting resorption (P<0.05). Patients with course of disease ≤1 year, Komori type C, Iwabuchi type 1 and type 5, relatively higher RSI and without Modic changes of adjacent vertebral bodies were prone to resorption after LDH.ConclusionThe course of disease, Komori classification, Iwabuchi classification, RSI and Modic changes are the influencing factors of resorption of LDH. Patients with course of disease ≤1 year, Komori type C, Iwabuchi type 1 and type 5, relatively higher RSI, and without Modic changes of adjacent vertebral bodies are prone to resorption of LDH, which has certain guiding significance for clinical prediction of resorption.